Comparing broom conditions in curling: Measurements using ice topography - Balsdon, M.; Wood, J. (Proceedings, 2020)
The sport of curling is played on an ice surface with raised ice pebbles and uses curling rocks made of granite. The effect of sweeping is thought to straighten the rock`s projected curved path and increase the distance travelled. Recent anecdotes suggest that sweeping from the center of the running surface with the direction of rotation and curl is thought to increase the amount of curl, whereas sweeping against and opposite the curl is thought to decrease the amount of curl. The purpose of this study is to observe the topography of the ice surface while comparing scratch measurements from different broom materials. Nine conditions were replicated: nipped pebble, rock traversing the ice, and seven broom conditions. Replicas of the ice were created with vinyl polysiloxane and observed with an optical microscope. Roughness profiles of the replicas were measured, and broom materials were compared using data from an optical profiler.